Human Concepts In The Perspective of Islamic Educational Philosophy - Kun Nurachadijat; Daden Fikruzzaman; Helnafri Ankesa (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research aims to analyze human concepts from the perspective of Islamic educational philosophy. This type of research uses a qualitative approach with a literature study method. Data sources are quoted from credible pages such as Google Scholar and SINTA. Next, the data was analyzed and checked for validity through data triangulation. The results of this research conclude that human nature based on the Koran is called the terms basyar, insan/ins, and bani Adam. The integrity of humans biologically, psychologically and spiritually is seen as a creature that has all the potential so that it is able to become 'abd (servant of Allah) and caliph (leader on earth). Thus, understanding human nature is an essence that is the beginning of further understanding in understanding the implementation of Islamic education. Islamic education is a process of creating a conducive learning environment for students in order to realize the goals of Islamic education, namely developing students' potential, including their physical, biological potential and their soul potential (nafs, qalbu, aql).